THE INFLUENCE OF TALENT MANAGEMENT, CONTINUOUS IMPROVEMENT, AND PERFORMANCE APPRAISAL ON PRODUCTIVITY OF VETERINARY STAFF IN LARAS SATWA CLINIC - Ady Sasmita; Andini Nurwulandari; Irma Setyawati (PT. Jurnal Center Indonesia Publisher, 2026)
This systematic literature review examined 40 high-quality empirical studies to synthesize evidence regarding how talent management, continuous improvement, and performance appraisal influence employee productivity across organizational contexts. The findings reveal that talent management creates direct and moderated effects on employee productivity through organizational culture and employee involvement mechanisms. Continuous improvement methodologies, including Lean Six Sigma approaches, yield simultaneous improvements in both productivity and quality outcomes, with demonstrated effectiveness in service-oriented sectors. Performance appraisal systems enhance employee productivity through clarified performance expectations, developmental feedback, and strengthened accountability mechanisms. A critical finding is that integrating these three human resource management domains produces synergistic effects that exceed the sum of isolated interventions, demonstrating multiplicative rather than additive productivity gains through mutually reinforcing mechanisms. The 40 included studies employed balanced methodological approaches including quantitative surveys, structural equation modeling, qualitative investigations, and empirical case studies, with 65% published in 2024-2025 reflecting contemporary human resource management practices. This systematic evidence synthesis establishes that veterinary clinics implementing comprehensive integrated approaches addressing talent management, continuous improvement, and performance appraisal simultaneously would achieve superior productivity outcomes while addressing the profession's unique emotional labor demands and animal welfare responsibilities.